2016
DOI: 10.1088/0953-8984/28/25/255301
|View full text |Cite
|
Sign up to set email alerts
|

Bound states induced giant oscillations of the conductance in the quantum Hall regime

Abstract: We theoretically studied the quasiparticle transport in a 2D electron gas biased in the quantum Hall regime and in the presence of a lateral potential barrier. The lateral junction hosts the specific magnetic field dependent quasiparticle states highly localized in the transverse direction. The quantum tunnelling across the barrier provides a complex bands structure of a one-dimensional energy spectrum of these bound states, [Formula: see text], where p y is the electron momentum in the longitudinal direction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Dynamics and kinetics of electrons in 2DEG in the presence of a lateral barrier under magnetic field H was experimentally and theoretically investigated in the situation that the current flows along 9,10 and perpendicular 8,19 to the barrier in ballistic samples. In all these cases giant conductance oscillations have been shown to arise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamics and kinetics of electrons in 2DEG in the presence of a lateral barrier under magnetic field H was experimentally and theoretically investigated in the situation that the current flows along 9,10 and perpendicular 8,19 to the barrier in ballistic samples. In all these cases giant conductance oscillations have been shown to arise.…”
mentioning
confidence: 99%
“…The object of the present paper is to investigate transport properties of a dirty biased 2DEG with a lateral barrier under semiclassical magnetic field, the barrier being placed perpendicular to the current. In contrast to the ballistic situation considered in paper 19 the contribution of the conventional edge states to the conductance is neglected assuming the following inequalities being satisfied: ω H τ ≫ 1; L y ≫ l 0 (ω H τ ) where ω H = eH/mc and l 0 = v F τ are the cyclotron frequency and the electron free path length, respectively, while τ is the free path time and v F is the Fermi velocity. It is shown that the above-mentioned bands and gaps manifest themselves by giant oscillations of the transverse conductance with a change of the magnetic field of the gate voltage.…”
mentioning
confidence: 99%